Pengaruh Dukungan Orang Dekat terhadap Kepatuhan Minum Obat pada Orang dengan HIV/AIDS (ODHA) di Kabupaten Madiun - Puri Ratna Kartini; Agung Prabowo Wisnubroto; Yovita Aprilia Putri (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: The proper and correct ARV therapy requires social support, especially from family and close people, in order to be able to reduce negative impacts of the infection.Methods: This study is an observational-analytic study to analyze the influence of support from close people for adherence to taking ARV drugs in PLWH in Madiun district. The research design used in this study was cross sectional with purposive sampling technique. Data was taken through interviews with respondents without giving any treatment. The sample in this study were patients who had been diagnosed with HIV positive for more than 6 months in 2018 which was randomly selected. The research location is the working area of the Local AIDS Eradication Commission (KPAD) of Madiun district. The study was conducted for 7 months, starting from June to December 2018.Result: From the results of bivariate analysis, it was concluded that the support from close people has influence on medication adherence in PLHIV (p = 0.000).Conclusion : From this research, it is expected to be an input for the government in determining health policy, especially to increase the rate of compliance with medication for PLWHA in Madiun district.